PENERAPAN MODEL EXAMPLE NON EXAMPLE PADA MATERI PENCEMARAN DALAM UPAYA MENINGKATKAN RESPON SISWA DI KELAS VII.4 SMPN 1 TANJUNG BATU - Ardius Ahmad Kidan (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2014)
ABSTRACT: Learning on curriculum in 2013 applying scientific learning with student-centered learning. Teaching and learning activities (KBM) were carried out every day, is the life of a class. Most of the learning process gurulah more active than the students, and yet we find that many students who are the subject of learning, more responding in the presentation phase (core) in the form of responses asking, answering the questions we ask, or also responding from questions her classmates, while learning the curriculum in 2013 students are required to seek out their own learning materials. To improve the response of students on teaching and learning activities, as well as a supporting instrument in the assessment of attitudes in the curriculum in 2013, the researchers applied learning model example non example in the presentation of material contamination in this study. This type of research is Classroom Action Research with the research procedure as follows: implementation of action plan of action → reflection → → → observation action planning next cycle. Objectives to be achieved through this research are to: determine the response improvement in grade VII.4 SMPN1 TanjungBatu on the application of material contamination with non exsampelexsampel learning model. The research instrument used in this study are: Observation sheet contains five aspects of student responses were observed, namely: 1.mengajukan question, 2.menjawab question, according 3.Mengemukakan topics discussed ideas, ideas 4.menangapi polite manner, 5. Providing solutions. Data were analyzed quantitatively, to measure the percentage increase in student responses for each indicator and the average percentage of the response of the fifth aspect of the response in each cycle. The results of data analysis are then presented in the form of descriptive description. Indicators of successful action is if the average percentage of the value of the five aspects of attitude response ≥ 75% (Good). Based on research data obtained from the second cycle the average value of the attitude of the student responses from the five aspects of attitude response assessed was 77.02%. Based on these results, we conclude that the cooperative learning model through the example of non example in the matter of pollution can increase response VII.4 junior high school students in grade 1 Tanjung Batu. Keywords: Cooperative Learning Model Type Non Example Example, student response